EXPLORING ELEMENTARY TEACHERS’ PRACTICES WITH RESPONSE TO IWBS - Samsonova, Olga (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The purpose of this study is to examine how American elementary public school teachers perceive and use interactive whiteboards (IWBs). The qualitative case study method was used for this study. Nine teachers were selected for this study and the IWBs usage for at least a year was used as the criteria. Data were collected through 2 Skype or phone interviews and teachers’ lesson plan snapshots. As the results of the research, various themes on teachers’ experiences emerged. The results show that participants have positive attitudes towards IWBs and consider them helpful. However, teachers also stated about the need for additional planning time, professional development, technology support, and technology upgrades.